Development of bacterial blight and changes in biochemical components in the resistant and susceptible genotypes of clusterbean - and U. BURMAN, SATISH LODHA, P.C. MALI (Indian Phytopathology, 2002)
Development of bacterial blight (Xanthomonas campestris pv. cyamopsidis) was studied in five genotypes of clusterbean. Maximum blight intensity (76.6 per cent) and apparent infection rate (0.052) was recorded in Pus a Navbahar. Two sprays of streptocycline significantly reduced the blight intensity and infection rate in all the genotypes. Lesser change in soluble carbohydrate, protein and chlorophyll coupled with more change in phenols and peroxidase due to blight infection in HG 75 compared to Pusa Navbahar partly accounts for the bacterial blight resistance in HG 75.